Rock physics modelling of the carbonate reservoirs: A log-based algorithm to determine the pore aspect ratio - Falahat, Reza; Farrokhnia, Foroogh (Journal of applied geophysics, 2020)
Rock physics models play an important role in understanding the elastic behavior of saturated rocks, and in the quantitative interpretation of seismic data in the areas between well controls. Most of the rock physics models were developed for clastic reservoirs. However, estimation of elastic properties in the carbonate reservoirs have been criticized recently. The major challenge on these reservoirs are primarily due to the pore type variation and the presence of fractures across the rock matrix. To overcome this issue, an aspect ratio (the ratio between the minor and major axes of an ellipsoidal pore) of the pore space was defined to consider the geometry of pores. Aspect ratio has a significant impact on the velocity of the saturated rock, however its quantification on the reservoir scale remains a challenging subject. Aspect ratio is commonly estimated from thin section analysis, however, thin sections are not commonly available for the entire logged reservoir interval. Hence, a constant aspect ratio is typically allocated for each pore type within the target layer. Considering the variation of depositional setting with depth, as well as including the role of diagenetic processes on the carbonate rocks, allocating a single constant aspect ratio across the reservoir interval could introduce uncertainties. In this paper, we introduce a log-based algorithm to estimate a variable aspect ratio that can be applied over the entire length of the logged interval. This method is based on the diverse influence of different pore types on the velocity and density logs. In addition, we include the impact of pressure variation on Xu and Payne (2009) model. Utilizing our methodology, the velocity log is estimated in a carbonate reservoir. The estimated velocity log shows better match with the measured velocity log compared with Lee (2005) (improved Gassmann) and Xu and Payne (2009) models. There are however some disparities left in the reconstruction of the velocity profile that encourages to understand the carbonate reservoirs further. •A technique is introduced to calculate the aspect ratio of the reservoir rocks utilizing well logs.•Rock physics models of the carbonate reservoirs are critically reviewed.•The pressure impact is included on the carbonate rock physics modelling.•Variable aspect ratio by depth would significantly increase the accuracy of a rock physics model.